Use of Prophylactic Antibiotics in Third and Fourth Degree of Perineal Rupture - William Alexander Setiawan (Indonesian Journal of Perinatology, 2022)
Numerous studies have demonstrated how routine episiotomies can cause additional problems like poor postpartum sexual function, ongoing perineal pain, and increased anal sphincter damage resulting in flatus or fecal incontinence. To combat the high frequency of maternal labor morbidity, antibiotic prophylaxis is recognized as a method of intervention that can be applied. . On the other hand, several studies seem to support the use of preventive antibiotics in situations of severe perineal rupture. It is not advised to use antibiotics excessively due to the rising prevalence of their use, which increases the danger of antibiotic resistance. As a result, following a serious perineal tear, the use of prophylactic antibiotics is crucial to preventing infection and determining whether a side effect is present in the mother or infant. Therefore it is necessary to assess the effectiveness of antibiotic prophylaxis to reduce maternal morbidity and side effects of third and fourth-degree perineal rupture during vaginal delivery.